2022
DOI: 10.3390/molecules27196628
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of Phenolic Acids and Flavonoids from Buckwheat Biscuits Prepared from Flours Fermented by Lactic Acid Bacteria

Abstract: The literature reports that the consumption of common buckwheat (Fagopyrum esculentum Moench), exactly the polyphenols it contains, is associated with a wide spectrum of health benefits. Therefore, the determination of the bioaccessibility of phenolic acids and flavonoids from buckwheat biscuits formulated from liquid-state fermented flours (BBF) by selected lactic acid bacteria (LAB) after gastrointestinal digestion was addressed in this study. Bioaccessibility could be defined as the fraction of a compound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The buckwheat and quinoa were found to have significantly ( p < .05) higher antioxidant activity and TPC than other materials. The high antioxidant capacity of buckwheat may be due to both the significant concentration of conjugated polyphenols and the presence of flavonoids not found in other species such as rutin (Estivi et al, 2022; Zieliński et al, 2022). Alvarez‐Jubete et al (2010) reported that the TPC and antioxidant activity values of buckwheat were higher than those of other pseudocereals and cereals.…”
Section: Resultsmentioning
confidence: 99%
“…The buckwheat and quinoa were found to have significantly ( p < .05) higher antioxidant activity and TPC than other materials. The high antioxidant capacity of buckwheat may be due to both the significant concentration of conjugated polyphenols and the presence of flavonoids not found in other species such as rutin (Estivi et al, 2022; Zieliński et al, 2022). Alvarez‐Jubete et al (2010) reported that the TPC and antioxidant activity values of buckwheat were higher than those of other pseudocereals and cereals.…”
Section: Resultsmentioning
confidence: 99%
“…Bioaccessibility can be described as the portion of a compound that is released from the food matrix in the gastrointestinal tract and is available for absorption in the intestine. Nutritionally, measuring bioaccessibility offers valuable insights essential for selecting food matrices that optimize the nutritional quality of final food products [12]. Therefore, in vitro gastrointestinal digestion (IVGD) methods serve as valuable tools for assessing the potential in vivo impact of any modifications made to a food product's composition.…”
Section: Introductionmentioning
confidence: 99%